The Effect of Chitosan-Based Edible Coating on The Moisture Content, Texture, and Microbial Count of Chicken Sausages - Bastomy, Muhammad Alif; Rahmadhia, Safinta Nurindra (Faculty of Animal Science, Universitas Brawijaya, 2025)
Chicken sausage is a protein-rich processed meat product that is prone to spoilage, necessitating the use of preservatives for its preservation. One approach to enhance shelf-life is using an edible coating composed of shrimp chitosan for their antimicrobial properties. Chitosan, derived from shrimp shells, has antimicrobial and biodegradable properties, which may help safeguard chicken sausage against microbial spoilage and physical degradation throughout storage. This study aims to evaluate the effect of shrimp chitosan-based edible coatings in preserving sausage quality. The research followed three steps: sample preparation, coating application, and post-treatment analysis of total microbial count (TPC), texture, and moisture content. A Completely Randomized Design (CRD) was used, with two factors: chitosan levels (0g, 2.5g, 3g, and 3.5g) and storage time (0, 3, and 5 days) in sealed containers at room temperature. The results showed that both chitosan coating and storage duration influenced the moisture, with the untreated samples showing 75.2% moisture and the treated samples under 70%. In addition, storage time impacted various texture parameters, such as adhesiveness, crunchiness, fracture, cohesiveness, hardness, and gumminess, while the edible coating specifically affected cohesiveness and hardness. Microbial data indicated no significant coating or storage duration effects on total microbial count. In conclusion, using chitosan-based edible coatings on sausages can influence their physical quality; nevertheless, reformulation is necessary to reduce microbial proliferation.